KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PENCURIAN DENGAN MODUS PECAH KACA MOBIL DALAM PERSPEKTIF KRIMINOLOGI (Studi Kasus Putusan Pengadilan Negeri Stabat No. 404/Pid.B/2013/PN.Stabat) - Fickry Abrar Pratama; Ediwarman Ediwarman; Mahmud Mulyadi; Syamsul Arifin (Universitas Sumatera Utara, 2017)
ABSTRACT Thefts with modus operandi by breaking windshields happen frequently in Indonesia. Since it increases in number, research on it from the criminological perspective in necessary in order to find out the causing factors. The Penal law can be used as the means to overcome this theft. Overcoming this crime by penal law can be categorized into the forms of penal and non penal efforts. The objective of teh research is to find out the factors that constitute this theft and the policy of penal law to overcome it. The formulation of problems in the research are how the legal regulation are in regard to this theft, what the causing factors are, modus operandi are, and how the penal law policy is to overcome this theft.The method used in the research is the judicial normative method, namely a method based on the library study in order to obtain the materials that meet the requirements. The instruments of data gathering are guidelines of interviews and library study. According to the research result, the theft with modus operandi by breaking the windshields is categorized into a theft with aggravation which is regulated in the Article 363 of the Penal Law. Theaggravating element is that there is an effort from the perpetrators to break a thing that prevents them from conducting their action and it is conducted by more than 2 persons. The factors that cause the theft with modus operandi by breaking the windshields are habit, environment, and benefit. The policy of the penal law to overcome this kind of theft can be divided into the penal and non penal forms. These are divided again into pre-adjudication phase. The pre-adjudication phase is the phase of filing to the police before getting into phase of court session and the adjudication is the hearing of the theft perpetrator to the court. Meanwhile, in the non penal efforts, the police have made preventive efforts, such as, by patrolling at critical hours either while wearing casual clothes or uniform to prevent the occurence of the theft. Keywords: Penal Policy, Theft with Modus Operandi by Breaking the Windshields